The burden of Plasmodium vivax malaria - Battle, K (2015)
Plasmodium vivax is the most geographically widespread of the human malarias and is capable of causing severe debilitating disease. The parasite’s unique biology poses challenges to control of the disease and the understanding of its epidemiology. It is less researched and well understood than the more deadly P. falciparum. In this thesis, spatial relapse patterns and models of endemicity and clinical disease were applied to generate robust estimates of the P. vivax burden to address a key knowledge gap in malaria epidemiology. First, a review of the distribution of the parasite, its vectors and populations at risk found nearly one third of the global population living at risk, and more potential vectors than P. falciparum. In spite of low observed endemicity, the public health impact of P. vivax is likely to have been seriously underestimated in the past. To accurately define the burden of P. vivax it was necessary to improve understanding of one of the parasite’s most unique and challenging aspects, its ability to relapse. A meta-analysis of individual records of relapse showed that relapse periodicity varied systematically by geographic region and could be categorized by nine global regions. The nine regions were applied to a model to quantify the relationship between prevalence of infection and incidence of clinical disease. As relapse would have an influence on both measures, separate relationships were drawn for each relapse zone. The prevalence-incidence model was used to translate maps of predicted endemicity into measures of clinical burden. The evidence-base of P. vivax prevalence was poor in some regions and therefore a burden estimate based on surveillance reports was also derived. Reported cases must be adjusted for parameters such as under-reporting and treatment-seeking behaviours. A model used to fill gaps in treatment-seeking data available from national household surveys was developed to allow burden to be estimated using both cartographic modelling and surveillance reporting methods. To improve fidelity, the results of the two approaches were combined to enumerate P. vivax burden globally. The results and conclusions of these studies are discussed with recommendations for how these findings influence our understanding of P. vivax epidemiology and implications for future control and elimination efforts.